Nationalism in Popular Culture: Critical Discourse Studies on American and Indonesian Films - Herman Felani; Ida Rochani Adi; Ratno Lukito (Department of Communications, Universitas Islam Indonesia, 2020)
Many scholars have alarmed the rise of new extreme nationalism in many countries which is actively promoted by some important national and international leaders. This paper examines the discourses of nationalism in popular culture and compares them with the nationalism ideas as promoted by those political leaders. Assuming that popular culture represents the bedrock belief of the society, this study has investigated the ideology of nationalism in 10 American and 10 Indonesian films applying the discourse historical approach from Ruth Wodak and Martin Reisigl. This study has identified nine features of nationalism in American films, i.e. us against them, saving life of Americans versus taking life of enemies, individual versus institutional hero, hero as common people, anti war narratives, individual versus national interest, absence of governmental supports, white as the dominant, and superpower. While six main features of nationalism in Indonesian films are against poverty, against foreign power, against corruption, sacrifice and service for the nation, imagination as a nation, and developing the nation. This study concludes that the discourse of nationalism in American and Indonesian films do not in line with the nationalism ideas as proposed by the politicians or the government. While the politicians are campaigning new hostile nationalism, popular cultures are promoting nationalism with individual freedom and equality, striving for prosperity, and fighting poverty.Keywords: Discourse-Historical Approach; nationalism; new nationalism; popular culture; American film; Indonesian film.